2021
DOI: 10.1016/j.jagp.2020.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Social Disconnection in Late Life Mental Illness – Commentary From the National Institute of Mental Health

Abstract: Highlight Social disconnection – both objective social isolation as well as perceived social isolation (otherwise known as loneliness) – is a prevalent affliction among older adults, with profound effects on mental health. Mechanistic understanding of how mental illness contributes to, is exacerbated by, or is otherwise linked to social disconnection remains elusive, and therapeutic interventions which lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Thus, the disruption of their social activities also caused social disconnection and the feeling of loneliness among them. These are consistent with the findings of some previous non-COVIDrelated studies which have reported that social disconnection puts older people at greater risk for morbidity and mortality, and has significant effects on their mental health conditions [53,54]. Our study also reported the feelings of loss experienced by participants due to the deaths of families and friends during the COVID-19 pandemic, which have not been reported in previous COVID-related studies with older populations in other settings [24][25][26]45].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the disruption of their social activities also caused social disconnection and the feeling of loneliness among them. These are consistent with the findings of some previous non-COVIDrelated studies which have reported that social disconnection puts older people at greater risk for morbidity and mortality, and has significant effects on their mental health conditions [53,54]. Our study also reported the feelings of loss experienced by participants due to the deaths of families and friends during the COVID-19 pandemic, which have not been reported in previous COVID-related studies with older populations in other settings [24][25][26]45].…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the disruption of their social activities also contributed to social disconnection and the feeling of loneliness among them. These are consistent with the findings of some previous non-COVID-related studies which have reported that social disconnection puts older people at greater risk for morbidity and mortality, and has significant effects on their mental health conditions [ 66 , 67 ].…”
Section: Discussionsupporting
confidence: 92%
“…Large disease outbreaks are associated with increased mental health problems due to social disconnection through enforcement of stay-at-home orders, isolation, and unemployment [ 63 ]. Additionally, social disconnection either real or perceived is a primary risk factor for a suicidal attempt [ 64 ].…”
Section: Discussionmentioning
confidence: 99%